From Protectors to Perpetrators: The Role of the Nigerian State in Perpetuating Crime - Magadze, Tshimangadzo Oscar (International journal of criminal justice sciences, 2025)
The Nigerian state is constitutionally tasked with protecting its citizens and upholding the rule of law. However, persistent patterns of state-linked criminality suggest a troubling reversal of this mandate. Despite growing evidence of state involvement in criminal activities in Nigeria, there is limited analysis of how state structures themselves perpetuate crime through institutional mechanisms. This study addresses this gap by examining how the Nigerian state, through its institutions and actors, contributes to the perpetuation of crime. Grounded in state criminality theory, the research employs a qualitative content analysis of secondary data to identify specific institutional pathways through which state actors enable criminal activities. Findings reveal five interconnected mechanisms: (1) direct involvement of public officials in corrupt practices; (2) weaponization of security forces for political violence; (3) judicial complicity through selective enforcement; (4) collusion with organized crime networks; and (5) systematic undermining of oversight institutions. The study demonstrates that state-sponsored criminality in Nigeria is not just the result of individual misconduct but represents systemic institutional failure sustained by patronage networks. This research provides critical insights for developing targeted interventions to address state complicity in crime and strengthen Nigeria’s governance framework.